Assessment of Knowledge and Attitudes of School Teachers Regarding Emergency Management of an Avulsed Permanent Tooth of Southern Region of Saudi Arabia - Khan, Siraj DAA (Int J Clin Pediatr Dent, 2020)
AIM: An avulsion is defined as one of the most common dental injuries where the tooth is displaced completely from its socket, followed by trauma. The most important time in managing the avulsed tooth is the first few minutes and as children spend their most of waking time in school so the teacher is considering their immediate caregiver. Hence, this study was done to carry out the knowledge and attitude of school teachers regarding emergency management of avulsed permanent tooth in schools located in the southern region of Saudi Arabia. MATERIALS AND METHODS: The study was conducted at Najran School of Saudi Arabia. All teachers who are willing to participate in the study were involved. A questionnaire was made after reviewing several studies and was administered through emails to 318 teachers. The questionnaire consists of part I regarding demographic questions and part II information related to knowledge, action taken, education, and their way of managing the avulsed tooth at accident place. Statistics analysis was done using SPSS version 16. RESULTS: Fifty percent of the participants know about the tooth avulsion. Fifty percent of the teachers who get information from the school health dental program get the tooth back to the dentist. There is a significant association found between the source of information and choice of treatment. Fifty-nine percent of the participants do not know about the management of tooth avulsion. And workshop plan then 89% was interested to attend the training. CONCLUSION: The present study revealed that knowledge regarding the management of avulsed tooth is low among the school teachers. There is a strong need for a school health dental program for the management of avulsed teeth among the school teachers. HOW TO CITE THIS ARTICLE: Khan SDAA, Assiry AA, Al Yami SMH, et al. Assessment of Knowledge and Attitudes of School Teachers Regarding Emergency Management of an Avulsed Permanent Tooth of Southern Region of Saudi Arabia. Int J Clin Pediatr Dent 2020;13(6):644–649.